On irregular surfaces of general type wih K2=2ҳ+1 and pg=2 - Gentile, Tommaso; Oliverio, Paolo Antonio; Leone, Nicola (My University, 2009)
This thesis is devoted to one of the classic topics about algebraic surfaces: the classi cation of irregular surface of general type and the analysis their moduli space. To a minimal surface of general type S we associates the following nu- merical invariants: the self intersection of the canonical class K2S ; the geometric genus pg := h0(!S) the irregularity q := h0( 1 S) = h1(OS). A surface S is called irregular if q > 0. By a theorem of Gieseker the coarse moduli space Ma;b corresponding to minimal surfaces with K2S = a and pg = b is a quasi projective scheme, and it has nitely many irreducible components. The above invariants determine the other classical invariants: the holomorphic Euler{Poincar e characteristic (S) := (OS) = 1 􀀀 q + pg; the second Chern class c2(S) of the tangent bundle which is equal to the topological Euler characteristic e(S) of S. The classical question that naturally rises at this point is the so{called geographical question, i.e., for which values of a; b is Ma;b nonempty? The answer to this question is obviously non trivial. There exists the following inequalities holding among the invariants of minimal surfaces of general type: K2S ; 1; K2S 2pg 􀀀 4 (Noether's inequality); if S is an irregular surface, then K2S 2pg (Debarre's inequality); K2S 9 OS (Miyaoka{Yau inequality). Thus = 1 is the lowest possible value for a surface of general type. By the Miyaoka{Yau inequality, we have that K2S 9, hence by the Debarre's inequality we get q = pg 4. All known results about the classi cation of such surfaces are listed in [MePa, Section 2.5 a]. If K2S = 2 , we have that necessarily q = 1. Since in this case f : S 􀀀! Alb(S) is a genus 2 bration, by using the fact that all bres are 2{connected, the classi cation was completed by Catanese for K2 = 2, and by Horikawa in [Hor3] in the general case. Catanese and Ciliberto in [CaCi1] and [CaCi2] studied the case K2 = 2 +1, with = 1. So in this case, by the above inequalities we get that the surfaces have the following numerical invariants: K2S = 3 and pg = q = 1: The classi cation of such surfaces was completed by Catanese and Pig- natelli in [CaPi]. The main tool for this classi cation is the structure theorem for genus 2 bration, which is proved in the same work. For 2 the situation is far more complicated and not yet studied. We consider in this thesis the case = 2. So our surfaces have the following numerical characters K2S = 5, pg = 2, q = 1: By a theorem of Horikawa, which a rms that for an irregular minimal surface of general type with 2 K2 8 3 , the Albanese map f : S 􀀀! Alb(S) 2 induces a connected bration of curves of genus 2 over a smooth curve of genus q, we have that in the considered case a bration f : S 􀀀! B over an elliptic curve B and with bres of genus 2. So we can use the results of Horikawa{Xiao and most of all those of Catanese{Pignatelli to face the challenge to completely classify all surface with the above numerical invariants. Their approach is of algebraic nature and in particular is based on a new method for studying genus 2 bration, basically giving generators and relations of their relative canonical algebra, seen as a sheaf of algebras over the base curve B. Our main results are as follows. First at all we studied the various possi- bilities for the 2{rank bundle f !S. We have that f !S can be decomposable or indecomposable. In the rst case the usual invariant e, associated to f !S by Xiao in [Xia1] can be equal to 0 or 2. We prove that the case e = 2 does not occur. Subsequently we study the case e = 0 with f !S decomposable. In such case we divide the problem in various subcases. For each such subcase we study the corresponding subspace of the moduli space M of surfaces with K2 = 5, pg = 2 e q = 1. By using the following formula: dimM 10 􀀀 2K2 + pg = 12 we can consider only the strata of dimension greater than or equal to 12. We proved that almost all the strata has dimension 11, so they don't give components of the moduli space. The most important result is that, for the so-called strata V II, we have the following theorem. Theorem 0.1. (i) MV II;gen is non-empty and of dimension 12; 3 (ii) MV II2 is non-empty and of dimension 13. References [CaCi1] F. Catanese, C. Ciliberto, Surfaces with pg = q = 1, Problems in the Theory of Surfaces and Their Classi cation, Cortona, (1988), Sympos. Math., SSSII, Academic Press, London, (1991), pp. 49-79. [CaCi2] F. Catanese, C. Ciliberto, Symmetric products of elliptic curves and surfaces of general type with pg = q = 1, J. Algebraic Geom. 2, (3) (1993), 389-411. [CaPi] F.Catanese, R. Pignatelli, Fibrations of low genus, I , Ann. Sci. Ecole Norm. Sup., (4) 39 (2006), 1011{1049. [Hor3] E. Horikawa, Algebraic surfaces of general type with small c21 , V, J. Fac. Sci. Univ. Tokyo Sect. I A. Math. 283 (1981), 745-755. [MePa] M. Mendes Lopes, R. Pardini, The geography of irregular surfaces, e-print arXiv : 0909:5195 (2009). [Xia1] Xiao, G., Surfaces br ees en courbes de genre deux, Lecture Notes in Mathematics, 1137, Springer-Verlag, Berlin, (1985), x+103 pp.
Dottorato di Ricerca in: Matematica ed Informatica, Ciclo XXI,a.a. 2008-2009
Keywords: Geometria algebrica; Superfici algebriche; Spazi geometrici; Moduli